Representation Of Nationalism In Wonderland Indonesia Video Clip (Charles Sanders Pierce Semiotic Analysis) (Pena Cendekia Insani, 2022)
The phenomenon of the decline of nationalism in Indonesia looks increasingly worrying, especially for the younger generation. This gave birth to the idea of ??Alffy Rev to make one of the video clips for Alffy Rev ft. Novia Bacmid entitled Wonderland Indonesia. The purpose of this study was to determine the representation of the sign of nationalism and to find out the expression of the meaning of nationalism in the Wonderland Indonesia video clip. This study uses a qualitative research method through the semiotic approach of Charles Sanders Peirce, in the form of a triangle theory of meaning; Representement, Object, and Interpretant, to show the sign and meaning of nationalism in the video clip. The result of this research is the message of nationalism in the music video